2015
DOI: 10.1007/s00436-015-4662-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical effects of botanical extract from Piper nigrum Linn (Piperaceae) against the dengue vector Aedes aegypti Liston (Diptera: Culicidae)

Abstract: The leaves of Piper nigrum L. (Piperaceae) were evaluated for chemical constituents and mosquito larvicidal activity against the larvae of Aedes aegypti. GC and GC-MS analyses revealed that the crude extracts contain 16 compounds. Thymol (20.77%) and ç-elemene (10.42%) were identified as the major constituents followed by cyclohexene, 4-ethenyl-4-methyl-3-(1-methylethenyl)-1-(1 methylethyl)-, (3R-trans) (7.58%), 4,6-octadienoic acid, 2-acetyl-2-methyl-, ethyl ester (6.98), 2(3H)-furanone, 3,4-bis(1,3-benzodiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 69 publications
(68 reference statements)
2
29
0
Order By: Relevance
“…Carboxyl-esterases (EC3.1.1.1) are non-specific omnipresent enzymes that are associated to the major "endogenous" functions in insects, which hydrolyze a different carboxylic-acid ester (Lija-Escaline et al, 2015). Generally, the metabolic pathway of these enzymes was targeted by the chemical pesticides, especially the fourth generation class of Pyrethroids, which acts on the voltage sensitive sodium channels and blocks the mosquito nervous system (Hong et al, 2014).…”
Section: Impact Of Phytochemicals On Detoxifying Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Carboxyl-esterases (EC3.1.1.1) are non-specific omnipresent enzymes that are associated to the major "endogenous" functions in insects, which hydrolyze a different carboxylic-acid ester (Lija-Escaline et al, 2015). Generally, the metabolic pathway of these enzymes was targeted by the chemical pesticides, especially the fourth generation class of Pyrethroids, which acts on the voltage sensitive sodium channels and blocks the mosquito nervous system (Hong et al, 2014).…”
Section: Impact Of Phytochemicals On Detoxifying Enzymesmentioning
confidence: 99%
“…Plant extracts and their derivatives have been widely reported to decrease the levels of carboxylesterase (α-β-carboxylesterase) level in the Ae. aegypti larva (Koodalingam et al, 2014;Lija-Escaline et al, 2015). Besides exhibiting larvicidal activity Alangium salvifolium, also substantially reduced the levels of α, β-carboxylesterase as well as superoxide dismutase (SOD) in Ae.…”
Section: Impact Of Phytochemicals On Detoxifying Enzymesmentioning
confidence: 99%
“…Several studies have demonstrated that this insecticidal activity is related to the presence of piperine and its derivatives (19) (20) (21) (22) . The development of any device from natural products with a potential insecticidal application, such as P. nigrum, requires a standardized extract of the main active component to be obtained to ensure both effectiveness and safety (30) .…”
Section: Discussionmentioning
confidence: 99%
“…After this period, activity decreased, which was attributed to degradation of the active ingredients (19) . However, it is worth noting that PnE has a higher duration of residual activity compared with other natural products such as copaiba oil and andiroba, a characteristic of interest for the incorporation into CRD (43) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation